Eighteenth-Century Land Speculation at the Margins of the Anglo-American World - Dewar, David (History compass, 2007)
Sometimes, by looking closely at one emblematic life we can see the ways in which historical dynamics work themselves out. Such is the case with George Morgan and his pursuit of land in the trans-Appalachian west. During the late eighteenth century he was, like many others, a fur trader, a diplomat, and a partner in a variety of land speculation schemes west of the Appalachian Mountains. As Americans of European extraction moved farther west, Morgan applied the trans-Appalachian speculation model in a unique manner and attempted to gain vast wealth and political power by obtaining rights to land west of the Mississippi River in Spanish Louisiana. In the end, his attempts to settle land and create a new society west of the Mississippi River extended, expedited, and facilitated the spread of Anglo-American settlements across the nation during the nineteenth century.